Business Development Strategy for Snack Processing in Micro Industries through Strengthening Marketing Aspects - Arbainah, Siti -; Handayani, Jati -; Sugiarti, Sugiarti - (Politeknik Negeri Semarang, 2019)
Kendal's specialty snacks are one of the culinary heritages that need to be preserved. Very reasonable to be developed. The purpose of this study is to formulate a business development strategy by increasing strengths and reducing the weaknesses of marketing aspects to seize available market opportunities. The object of the research is the micro industry member of KUB Bina Usaha in Jambearum Patebon Tourism Village, Kendal Regency, which produces Kendal typical snacks